Client-Server Library Index Automation System - Repianskyi, N.; Rak, T. (Видавництво Львівської політехніки, 2022)
The goal of the work is to develop a clientserver software system for library index automation, which consists of the user interface, presented as a web page, back-end server layer, and database. The problem of developing a library index automation system has been considered. The developed structure of the library index automation system has been presented. The structure of the library index automation system database has been proposed. The features of designing the user interface of the library index automation system have been considered. The general algorithm of the library index automation system and the system's class diagram have been presented. To make sure that the developed system is secure and stable development testing as well as stress testing have been performed.
Keywords: client-server architecture; software system; library; automation; database; Java; Spring; Online public access catalog